An examination of the direct and indirect effect of self-objectification and disordered eating. (13th April 2021) - Giles, S.; Rabinowicz, J.; Raux, C.; Fuller-Tyszkiewicz, M.; Krug, I.
Abstract : Introduction: Objectification theory argues that self-objectification confers risk for disordered eating (DE) both directly, and indirectly through a cascade of negative psychological consequences (e.g. low mood and self-conscious body monitoring). Robust cross-sectional evidence supports these relationships. However, these cross-sectional studies do not provide evidence for the complex intraindividual psychological processes outlined in objectification theory which purportedly contribute to DE. Objectives: Using an ecological momentary assessment design, the current study investigated the direct within-person effect between state self-objectification and DE and examined the indirect within-person effect of negative mood and body comparisons, on the relationship between state self-objectification and DE. Methods: Two-hundred female participants (M=20.43 years, SD=4.60) downloaded a smartphone app which assessed momentary experiences of self-objectification, mood, body comparisons, and DE six times per day at random intervals for seven days. Results: Indicated that self-objectification significantly predicted DE behaviours [95% CI 0.01, 0.03] and body comparisons [95% CI 0.32, 0.41]. However, the indirect effect of body comparisons on the relationship between state self-objectification and DE was not significant [95% CI -0.01, 0.00]. In the second mediation model, self-objectification significantly predicted DE behaviours [95% CI 0.01, 0.03], but did not significantly predict mood [95% CI -0.06, 0.03]. Similarly, the indirect effect of mood on the relationship between state self-objectification and DE was not significant [95% CI -0.00, 0.00]. Conclusions: These results enhance our understanding of objectification theory and suggest that self-objectification confers risk to DE directly. However, our findings do not support the indirect effect of self-objectification on DE through low mood or body comparisons. Disclosure: No significant relationships.